Effectiveness of electronic trials against children in conflict of the law at boyolali district court - Eka Yektiningsih; Natangsa Surbakti; Nuria Siswi Enggarini; Peggy Dian Septi Nur Angraini (Trigin Publisher, 2023)
The Covid 19 pandemic that has spread throughout the world has had an impact on the course of the judicial process. Empirical juridical research using qualitative descriptive data analysis methods and deductive conclusions aims to describe the effectiveness of the implementation of electronic based trials for children in conflict with the law. The electronic based trial law policy is based on Supreme Court Regulation Number 1 of 2019 concerning Electronic Administration of Cases and Trials in Courts and Supreme Court Regulation Number 4 of 2020 concerning Administration and Trial of Criminal Cases in Electronic Courts. At the implementation level, the Boyolali Regency Class IB District Court for electronic juvenile criminal cases was effective in 2020, holding 11 (eleven) electronic trials of juvenile criminal cases. However, there were still non technical obstacles during the trial. Therefore, the implementation of electronic criminal justice for children needs to be supported by adequate electronic systems and devices as stated in the Decree of the Director General of the General Courts of the Supreme Court of the Republic of Indonesia Number 1693/DJU/SK/HM02.3/12/2020 concerning Standardization of Trial Facilities and Infrastructure Online (on the network) in general courts, including juvenile justice. Keywords : Child, Legal Effectiveness, Electronic Justice